Pengaruh Biological Asset Intensity, Kepemilikan Manajerial, Ukuran Perusahaan Dan Profitabilitas Terhadap Pengungkapan Aset Biologis (Studi Pada Perusahaan Agrikultur Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2018-2021) - Wahdan Arum Inawati; Sitti Farikha Tenri Pada (Universitas Hamzanwadi, 2023)
Biological assets are the most unique part of an agricultural company so that they become the most meaningful assets and this agricultural company operates as a biological transformation of assets owned by flora and fauna except for productive plants. This study aims to analyze biological asset intensity, managerial ownership, company size, and profitability on the disclosure of biological assets (case studies on agricultural companie listed on the IDX 2018-2021). This study falls under the quantitative research category, focusing on agricultural companies that were listed on the IDX between 2018-2021, with a total of 11 companies in the sample. The researchers utilized purposive sampling and panel data regression analysis with the assistance of Eviews 12. The findings indicate that disclosure of biological assets is influenced by biological asset intensity, managerial ownership, company size, and profitability when considered together. However, biological asset intensity, managerial ownership, and company size have no significant effect on the disclosure of biological assets when examined separately. On the other hand, profitability has a considerable positive impact on the disclosure of biological assets among agricultural companies listed on the IDX between 2018-2021